Therapeutic Approaches in COVID-19 Patients: The Role of the Renin-Angiotensin System - Farzaneh Ketabchi; Sina Jamzad (Canadian Respiratory Journal)
Two and a half years after COVID-19 was first reported in China, thousands of people are still dying from the disease every day around the world. The condition is forcing physicians to adopt new treatment strategies while emphasizing continuation of vaccination programs. The renin-angiotensin system plays an important role in the development and progression of COVID-19 patients. Nonetheless, administration of recombinant angiotensin-converting enzyme 2 has been proposed for the treatment of the disease. The catalytic activity of cellular ACE2 (cACE2) and soluble ACE2 (sACE2) prevents angiotensin II and Des-Arg-bradykinin from accumulating in the body. On the other hand, SARS-CoV-2 mainly enters cells via cACE2. Thus, inhibition of ACE2 can prevent viral entry and reduce viral replication in host cells. The benefits of bradykinin inhibitors (BKs) have been reported in some COVID-19 clinical trials. Furthermore, the effects of cyclooxygenase (COX) inhibitors on ACE2 cleavage and prevention of viral entry into host cells have been reported in COVID-19 patients. However, the administration of COX inhibitors can reduce innate immune responses and have the opposite effect. A few studies suggest benefits of low-dose radiation therapy (LDR) in treating acute respiratory distress syndrome in COVID-19 patients. Nonetheless, radiation therapy can stimulate inflammatory pathways, resulting in adverse effects on lung injury in these patients. Overall, progress is being made in treating COVID-19 patients, but questions remain about which drugs will work and when. This review summarizes studies on the effects of a recombinant ACE2, BK and COX inhibitor, and LDR in patients with COVID-19.